Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fnut.2021.708096
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum TWK10 Attenuates Aging-Associated Muscle Weakness, Bone Loss, and Cognitive Impairment by Modulating the Gut Microbiome in Mice

Abstract: In humans, aging is characterized by the progressive decline in biological, physiological, and psychological functions, and is a major risk factor in the development of chronic diseases. Therefore, the development of strategies aimed at attenuating aging-related disorders and promoting healthy aging is critical. In a previous study, we have demonstrated that Lactobacillus plantarum TWK10 (TWK10), a probiotic strain isolated from Taiwanese pickled cabbage, improved muscle strength, exercise endurance, and overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 95 publications
(117 reference statements)
0
11
1
Order By: Relevance
“…Studies indicated that the beneficial effects of Lactobacillus supplementation on bone mass may be associated with increased generation of SCFAs in the gut. [ 23 , 24 ] However, the results here do not support this mechanism, indicating that other potential mechanisms related to Lactobacillus may play a crucial role in promoting bone mineralization in OVX rats. Li et al.…”
Section: Discussioncontrasting
confidence: 72%
“…Studies indicated that the beneficial effects of Lactobacillus supplementation on bone mass may be associated with increased generation of SCFAs in the gut. [ 23 , 24 ] However, the results here do not support this mechanism, indicating that other potential mechanisms related to Lactobacillus may play a crucial role in promoting bone mineralization in OVX rats. Li et al.…”
Section: Discussioncontrasting
confidence: 72%
“…Oral administration of B. longum NK46 or L. plantarum C29 increases cognitive decline in Ag and Tg mice by inducing NF-κB-mediated BDNF expression [ 15 , 17 ]. L. plantarum TWK10 also alleviates aging-related CI in mice by regulating gut microbiome [ 40 ]. Lactobacillus fermentum JDFM216 also alleviates cognitive behavior in aged mice [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the administration of Lactiplantibacillus plantarum TWK10 (TWK10) exerted beneficial effects on improving exercise performance, increasing muscle mass and strength in both mice and humans, and attenuating ageassociated cognitive decline and loss of bone mass in mice. We further found that long-term TWK10 administration did not result in significant histological changes in the organs of mice or alterations in hematological and biochemical parameters in humans [19][20][21][22]. In this study, we comprehensively assessed the safety of TWK10 as a probiotic for human consumption using both in vitro and in vivo approaches.…”
Section: Introductionmentioning
confidence: 94%